2012
DOI: 10.1016/j.febslet.2012.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of xenosiderophores in Bacillus subtilis occurs with high affinity and enhances the folding stabilities of substrate binding proteins

Abstract: a b s t r a c tSiderophores play an essential role in a multitude of microbial iron acquisition pathways. Many bacteria use xenosiderophores as iron sources that are produced by different microbial species in their habitat. We investigated the capacity of xenosiderophore uptake in the soil bacterium Bacillus subtilis and found that it employs several substrate binding proteins with high specificities and affinities for different ferric siderophore species. Protein-ligand interaction studies revealed dissociati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 42 publications
1
23
3
Order By: Relevance
“…Instead, P. fluorescens very likely utilizes the S. ambofaciens siderophores desferrioxamine B and coelichelin as xenosiderophores, thanks to its FoxA receptor. In contrast to most studies, in which the use of xenosiderophores was revealed indirectly through the addition of purified siderophore to the growth medium (44)(45)(46)(47), binding affinity assays (11,48), or native PAGE and surface plasmon resonance (49) or with labeled iron (11,50,51), we revealed potential iron piracy through a direct interaction between a Gram-positive and a Gram-negative bacterium. This potential piracy likely occurs only in one direction.…”
Section: Discussioncontrasting
confidence: 91%
“…Instead, P. fluorescens very likely utilizes the S. ambofaciens siderophores desferrioxamine B and coelichelin as xenosiderophores, thanks to its FoxA receptor. In contrast to most studies, in which the use of xenosiderophores was revealed indirectly through the addition of purified siderophore to the growth medium (44)(45)(46)(47), binding affinity assays (11,48), or native PAGE and surface plasmon resonance (49) or with labeled iron (11,50,51), we revealed potential iron piracy through a direct interaction between a Gram-positive and a Gram-negative bacterium. This potential piracy likely occurs only in one direction.…”
Section: Discussioncontrasting
confidence: 91%
“…subtilis has six siderophore-specific SBPs (28). These proteins are tethered to the outside of cells, where they bind iron-bound siderophores for uptake into the cells through ABC-type transporters.…”
Section: Resultsmentioning
confidence: 99%
“…subtilis is able to pirate multiple classes of siderophores using its diverse range of siderophore uptake systems (28). To determine whether promotion of sporulation gene expression was specific to enterobactin or was a general response to xenosiderophores, we tested the activities of multiple siderophores in our microcolony lawn assay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations